Optimisation of tourism object functions as a means of introducing Islam in Indonesia - Jamal, Khairunnas; Putra, Afriadi; Nur, Afrizal; Siregar, Syafril (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper discusses the optimisation of tourism object functions as a means of introducing Islam in Indonesia. This study is important because up until now, tourist attractions have only been utilised for its leisure purposes. One approach that can be taken to achieve the optimisation is by maximising the potential of attractions that are visited by many foreign tourists, such as the Gili Trawangan Island, Lombok, West Nusa Tenggara. To achieve the objectives, we have carried out a field research utilising the method of observation, interviews and, documentation for data collection. This research concludes that the mosque can be optimised to function not only as a primary place of worship but also as a medium for da'wah for Muslims, e.g a source of information, a place to ask questions and a platform to explore moderate Islamic teachings; and (ii) that the mosque as the main worship facility on Gili Trawangan Island can be used as a very effective means of introducing the teachings of Islam to foreign tourists.